2020
DOI: 10.20884/1.jm.2020.15.1.585
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antiproliferative Activity and Molecular Docking Studies of 1,3,5-Triaryl Pyrazole Compound as Estrogen α Receptor Inhibitor Targeting MCF-7 Cells Line

Abstract: This research has been successfully synthesized three compounds of 1,3,5-triaryl pyrazole derivatives by two steps reaction. Firstly, pyrazoline (4a-c) compound was obtained by one-pot reaction of aromatic ketones, aldehyde and hydrazine in basic condition. Then, pyrazole (5a-c) compound was obtained by oxidative aromatization of compound 4 in the presense of acetic acid. Chemical structure of predicted molecules was confirmed by FTIR, NMR and HRMS spectroscopy data analysis. Antiproliferative activity of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The FTIR spectra of 4 a – g showed characteristic bands at 1601–1610 cm −1 which attributed to the υ C‐H band of the aromatic groups in the pyrazole network [22] . 1 HNMR spectra displayed a singlet at 7.09–7.29 ppm which corresponded to pyrazole configuration [39] . 13 CNMR spectra displayed sharp signals at 105.5–109.7 ppm attributed to pyrazole confirmation [35] .…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of 4 a – g showed characteristic bands at 1601–1610 cm −1 which attributed to the υ C‐H band of the aromatic groups in the pyrazole network [22] . 1 HNMR spectra displayed a singlet at 7.09–7.29 ppm which corresponded to pyrazole configuration [39] . 13 CNMR spectra displayed sharp signals at 105.5–109.7 ppm attributed to pyrazole confirmation [35] .…”
Section: Resultsmentioning
confidence: 99%
“…The reaction mechanism of one-pot pyrazoline synthesis is initiated by the formation of chalcone compound as intermediate via Claisen-Schmidt reaction. Subsequently, the cyclization reaction occurs between chalcone with hydrazine to form pyrazoline compounds (Herfindo et al, 2020).…”
Section: Results and Discussion Synthesismentioning
confidence: 99%
“…In previous work, we have synthesized 1,3,5-triaryl pyrazole with anti-proliferative activity against MCF-7 cell line (Herfindo et al, 2020). However, that work showed that the compounds are not active as anti-proliferative.…”
Section: Introductionmentioning
confidence: 98%
“…[14] Pyrazole represents one of the essential nitrogen-containing heterocycle, featured predominantly in numerous FDA-approved drugs (Figure 1) such as Avapritinib, Asciminib, Crizotinib, Darolutamide, Encorafenib, Erdafitinib, Pralsetinib, Pirtobrutinib, Pyrazofurin, and Ruxolitinib. [15] Pyrazole derivatives have become key pharmacophores in targeting various signaling molecules and transcriptional factors within the cancer pathway, [16] such as ER-α, [17,18] aromatase, Epidermal Growth Factor Receptor (EGFR), [19,20] and HER-2. [21] Studies by S. R. Stauffer et al have extensively explored pyrazole core substitutions to identify an optimized core, propyl-pyrazole triol (PPT), for high-affinity ER binding.…”
Section: Introductionmentioning
confidence: 99%
“…(Scheme 1) General synthesis of compound 8 a-n. Chemicals and conditions: (i) ethanol, acetic acid, warm, 1-4 h (ii) POCl 3 & DMF at 0 °C, 2-5 h, and neutralized through K 2 CO 3 ; (iii) K 2 CO 3 , Acetone, 0 °C -r.t., 4-5 h; (iv) aq.40 % NaOH & ethanol, r.t.,[12][13][14][15][16][17][18][19][20][21][22][23][24]…”
mentioning
confidence: 99%